2020
DOI: 10.3390/systems8010008
|View full text |Cite
|
Sign up to set email alerts
|

Would You Fix This Code for Me? Effects of Repair Source and Commenting on Trust in Code Repair

Abstract: Automation and autonomous systems are quickly becoming a more engrained aspect of modern society. The need for effective, secure computer code in a timely manner has led to the creation of automated code repair techniques to resolve issues quickly. However, the research to date has largely ignored the human factors aspects of automated code repair. The current study explored trust perceptions, reuse intentions, and trust intentions in code repair with human generated patches versus automated code repair patche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Tyler et al [34] show that developers in general tend to trust more in patches produced by humans than automatic program repair techniques. Similar results are the ones obtained by Alarcon et al [1], indeed, they report that programmers find human repairs more trustworthy than the ones generated by GenProg. The study by Cambronero et al [3] investigates how humans are used to use the patches automatically generated by program repair techniques.…”
Section: Empirical Studies Investigating How Humans Use Automatic Pat...supporting
confidence: 89%
“…Tyler et al [34] show that developers in general tend to trust more in patches produced by humans than automatic program repair techniques. Similar results are the ones obtained by Alarcon et al [1], indeed, they report that programmers find human repairs more trustworthy than the ones generated by GenProg. The study by Cambronero et al [3] investigates how humans are used to use the patches automatically generated by program repair techniques.…”
Section: Empirical Studies Investigating How Humans Use Automatic Pat...supporting
confidence: 89%
“…Ryan et al (2019) show that developers in general tend to trust more in patches produced by humans than automatic program repair techniques. Similar results are the ones obtained by Alarcon et al (2020), indeed, they report that programmers find human repairs more trustworthy than the ones generated by GenProg. The study by Cambronero et al (2019) investigates how humans are used to use the patches automatically generated by program repair techniques.…”
Section: Empirical Studies Investigating How Humans Use Automatic Pat...supporting
confidence: 86%
“…The survey results also provide indications of what might increase developer trust in automatically generated patches, such as test cases, explanations of the patch, and evidence of patch correctness. Alarcon et al's experimental study also considered trust in APR, and found that the source of the repair (human vs. automated) had significant influence on trust perceptions and intentions, participants having higher trust in human repairs than automated repairs [22]. Both these studies demonstrate recent advances in human factors research in APR.…”
Section: Related Workmentioning
confidence: 96%